Literature Review: Bulletin Media in Learning as a Literacy Resource in Strengthening the National Literacy Movement Program - Ahmar, Dewi Satria; Azzajjad, Muhammad Fath (Athena: Journal of Social, Culture and Society, 2024)
Through a survey of numerous articles connected to bulletin media in learning, this study intends to provide information on the utilization and development of bulletins as a learning medium. This study is classified as a literature review. The information data used was collected from scientific journals accredited by the Science and Technology Index (SINTA). The information was gathered by analyzing published data from 2016 through 2022. Researchers examined, analyzed, and collaborated to evaluate, assemble, and review the results. Choosing nine journal papers that investigate the use and development of bulletins as learning media. 9 articles were picked at random to represent the chosen theme research, namely the use and development of bulletin media. The literature review includes information on the title of the scientific article, the author, the source of the journal publication, the methods used, the findings, and the review's recommendations in describing specific concepts and explanations that are still missing from the essence of the scientific article. This scientific article review is meant to serve as a source of inspiration for educational progress through the use of various media in molding excellent education in accordance with national goals